A conceptual hydrogeological model of ophiolitic aquifers (serpentinised peridotite): The test example of Mt. Prinzera (Northern Italy). Issue 5 (23rd December 2016) - Segadelli, Stefano; Vescovi, Paolo; Ogata, Kei; Chelli, Alessandro; Zanini, Andrea; Boschetti, Tiziano; Petrella, Emma; Toscani, Lorenzo; Gargini, Alessandro; Celico, Fulvio
Abstract: The main aim of this study is the experimental analysis of the hydrogeological behaviour of the Mt. Prinzera ultramafic massif in the northern Apennines, Italy. The analysed multidisciplinary database has been acquired through (a) geologic and structural survey; (b) geomorphologic survey; (c) hydrogeological monitoring; (d) physico‐chemical analyses; and (e) isotopic analyses. The ultramafic medium is made of several lithological units, tectonically overlapped. Between them, a low‐permeability, discontinuous unit has been identified. This unit behaves as an aquitard and causes a perched groundwater to temporary flow within the upper medium, close to the surface. This perched groundwater flows out along several structurally controlled depressions, and then several high‐altitude temporary springs can be observed during recharge, together with several perennial basal (i.e., low altitude) springs, caused by the compartmentalisation of the system because of high‐angle tectonic discontinuities.